The Natural Resource Boom and the Uneven Fall of the Labor Share - Andrés O. Dávila; Manuel Fernandez Sierra; Hernando Zuleta (Institute of Labor Economics (IZA), 2021)
We study the effect of the upsurge of natural resources income from the commodity price boom of the 2000s on the functional distribution of income. To do so, we build a general equilibrium model of Dutch disease that characterizes how natural resource windfalls affect equilibrium factor shares. The theory suggests that the response of factor shares to exogenous changes in commodity prices depends on the relative intensity in which factors are used in the tradable and natural resource sectors. We construct estimates of income shares accruing to raw labor, human capital, physical capital, and natural resources, and quantify the effect of the resource boom on factor shares. For identification, we use a two-way fixed effects strategy and a differential exposure design to instrument commodity prices. We find that a natural resource boom negatively impacts the total labor, human capital, and physical capital shares, while the raw labor share remains unchanged. Our estimates suggest that the natural resource boom explains nearly 25.7 percent of the global decline of the total labor share during the 2000s. We also find a redistribution effect within labor income that indicates that the fall of the labor share was unevenly distributed against human capital.
Keywords: D33; F14; J31; O13; 330; labor share; factor income shares; natural resource boom; commodity price boom; dutch disease; human capital